Status Anak Angkat Sebagai Ahli Waris Menurut Hukum Adat Bali - I Made Rai Arya Suta Negara; Anak Agung Sagung Laksmi Dewi; I Wayan Werasmana Sancaya (Fakultas Hukum Universitas Warmadewa, 2024)
Land title certificates are the final result in the deed registration process: The adoption of a child who makes heirs to a child for his adoptive parents. Implementation of an adoption of children by implementing customary law, especially in terms of inheritance system. A child adopted by adoptive parents where the adoption of the child has the purpose of being a successor to offspring for his adoptive parents. The research will discuss 1) the legal rules of a child as the heir of Balinese customary law? And 2)what is the form of inheritance distribution related to the adoption of children in customary law in Bali?. The author will use normative legal type research. People in Bali in particular Indigenous peoples from ancient times have adopted a patrilineal family system, in terms of adoption of children carried out with the aim of maintaining the continuity of property in the continuity of a family descendant and in customary law in Bali in the inheritance system derived from ancestors in the form of heirlooms.